Ziemianki Królestwa Polskiego i polityka (przełom XIX i XX wieku). Konteksty, uwikłania, wybory - Kostrzewska, Ewelina Maria (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
The landladies of the Kingdom of Poland were involved in the world of politics in various degree determined by the general situation (social, political, economic) existing in the Kingdom of Poland at the end of the 19th and the beginning of the 20th century. The special feature of this period was the growing emancipation of women as well as the increasing influence of politics which meant the necessity of taking ideological choices. The landladies being entangled in the historical context of the period as well as the specific character of their own elitist environment, took part in the social and political life. They stated their opinions about the church and religion, the equality of public rights to vote and programmes of political parties. In case of increasing strife and divisions, the landladies developed their own way of dealing with politics, which contributed to the process of creating modern democracy. The process which was interrupted by the outbreak of World War I.